2017
DOI: 10.15829/1728-8800-2017-6-115-121
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Cardiovascular Mortality in Tomsk Inhabitants as a Typical City of Western Siberia

Abstract: национального исследовательского медицинского центра. Томск; 2 Медицинское объединение "Здоровье". Томск, Россия [Ефимова Е. В.*-к. м.н., главный врач клиники, Конобеевская И. Н.-к. м.н., лаборант-исследователь отделения популяционной кардиологии с группой научно-медицинской информации, патентоведения и международных связей, Максименко Г. В.-к. м.н., врач терапевт, пульмонолог, зав. дневным стационаром, Карпов Р. С.-д. м.н., профессор, академик РАН, научный руководитель института]. Цель. Изучить влияние курени… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…Over 24 years of observation (from 1982 to 2006), 491,188 deaths were recorded as part of the survey, with the cause of death being recorded for 99.3% of them. Estimates of the relative mortality risks obtained using the survey data have a significantly higher level of detail both by gender and age groups and by the list of diseases compared to similar Russian prospective mortality surveys (Plavinsky, Plavinskaya 2012; Konstantinov et al 2007;Efimova et al 2017).…”
Section: Datamentioning
confidence: 86%
See 1 more Smart Citation
“…Over 24 years of observation (from 1982 to 2006), 491,188 deaths were recorded as part of the survey, with the cause of death being recorded for 99.3% of them. Estimates of the relative mortality risks obtained using the survey data have a significantly higher level of detail both by gender and age groups and by the list of diseases compared to similar Russian prospective mortality surveys (Plavinsky, Plavinskaya 2012; Konstantinov et al 2007;Efimova et al 2017).…”
Section: Datamentioning
confidence: 86%
“…For example, according to the results of a prospective study of mortality among residents of St. Petersburg over the course of 30 years, mortality from all causes among men was for smokers more than double the mortality of never-smokers (Plavinsky, Plavinskaya 2012). A retrospective study of male mortality in Tomsk in 1990Tomsk in -2001 showed that between the ages 15-74, smoking increases the risk of death by 1.5 times, and at working age -more than 2 times (Efimova et al 2017). Female smoking is no less dangerous.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Показатели таблиц дожития и СОПЖ являются важнейшими медико-демографическими характеристиками, которые широко используются в качестве системных индикаторов уровня социально-экономического развития территорий, качества жизни и здоровья населения [2][3][4][5][6][7][8][9][10].…”
Section: Introductionunclassified